Grassland restoration measures alter soil methane uptake by changing community phylogenetic structure and soil properties. (December 2021) - Liu, Zhiying; Li, Huizhen; Wang, Tianqi; Huang, Nan; Huang, Zixuan; Luo, Yaqin; Yan, Wenbin; Baoyin, Taogetao
Highlights: Soil was a CH4 sink across all three grassland restoration measures. Shallow ploughing significantly enhanced soil CH4 uptake, but harrowing decreased. The rates of soil CH4 uptake related with plant phylogenetic diversity. Soil properties had positive or negative effects on CH4 uptake rate. Shallow ploughing plays a vital role in sustaining grassland multifunctionality. Abstract: Grassland restoration can play a critical role in regulating ecosystem carbon cycling, especially for changes in methane (CH4 ) flux. However, how grassland restoration measures affect soil CH4 flux remains poorly understood. Here, we investigated the relationships between soil CH4 flux and properties of both plant communities and soil under different grassland restoration measures (shallow ploughing, harrowing and natural recovery) in a field experiment conducted during the growing season in a semiarid grassland in northern China using the static chamber method. Soil was a CH4 sink across all three restoration measures. Compared to natural recovery, shallow ploughing significantly enhanced and harrowing significantly decreased soil CH4 uptake. The rates of soil CH4 uptake were positively associated with litter production and belowground biomass and negatively associated with plant taxonomic and phylogenetic diversity. Soil temperature, NH4 + -N concentration, and soil organic matter quality had positive effects on CH4 uptake rate, but soil moisture and NO3 − -N concentration had negative effects on CH4 uptake rate. Our results elucidate the pathway through which shallow ploughing facilitates soil CH4 uptake in a semiarid grassland and thus highlights its role in sustaining ecosystem multifunctionality as a measure for grassland restoration.